Stress among Female Medical Students in selected Medical Colleges of Dhaka City in Bangladesh - Farzana, Nashid; Shahjahan, M; Nayan, Safia Khatun (Northern International Medical College Journal, 2017)
Background : Stress is bodys way of responding to any kind of change that requires a physical, mental or emotional adjustment. Medical students_are_subjected to stress by strenuous medical programs, which may have physical and psychological effects on their well-being. Objectives : To determine level of stress among 3rd and 4th year female medical students in selected medical colleges of Dhaka city. Materials and methods : Descriptive, cross sectional study was carried out on the female students of 3rd year and 4th year of Sir Salimullah Medical College and Northern International Medical College located in Dhaka city during January- March 2016. The medical colleges were selected using purposive sampling technique. Sample size was 296 female students and data were collected by self administered semi structured pretested questionnaire. PMSS scale (Perceived Medical School Stress Scale) was used to find out the level of stress among the respondents. Results : From the current study it was found that about 82% female medical students had moderate level of stress according to PMSS (Perceived Medical School Stress Scale), 6% and 12% had high level and low level of stress respectively. Statistically significant association was found between level of stress and medical college curriculum (p=0.000),academic environment (p=0.000), social and recreational life (p=0.000), worries about study and performance (p=0.004), worries about finance p=0.005), worries about accommodation (p=0.000). Conclusion : In this study, stress in different levels were found among all of the female medical students. About 82% female medical students had moderate level of stress according to PMSS (Perceived Medical School Stress Scale). The study also revealed that a statistically significant association between level of stress and medical college curriculum, academic environment ,social and recreational life, worries about study and performance, worries about finance and accommodation. Northern International Medical College Journal Vol.8(1) July 2016: 181-184